Challenges Facing Small and Medium Tourism Enterprises: A Case Study in Kuala Sepetang - Ong, Ke Shin; Chan, Ngai Weng; Dawood, Sharifah Rohayah Sheikh (European Publisher, 2019)
Tourism is increasingly being viewed as a development strategy for regional growth, especially in areas experiencing rural decline and economic contraction. In Malaysia, most of the rural tourism related firms are small and medium enterprises (SMEs). While the role of SMEs in destination development is widely studied, the opportunities and challenges facing tourism SMEs are underexplored. In this regard, this study aims to identify and explore the opportunities and challenges that rural tourism SMEs, particularly those faced by boat operators and strategies adopted to overcome these problems. Qualitative approach using in-depth interviews was adopted as a data collection strategy. The findings revealed that most of the boat operators based in Kuala Sepetang are male, with primary or secondary education. Reasons for the boat operators to ventured into tourism include to seek alternative income, to return to their hometown, or to satisfy their passion as a lifestyle entrepreneur. The main challenges the boat operators faced are (i) lack of qualified manpower; (ii) inadequate infrastructures; (iii) variable numbers of seasonal visitors; and (iv) competition among the boat operators.